Surprising Spin–Orbit Resonances of Rocky Planets - Henry D. A. Yuan; Yubo Su; Jeremy Goodman (The Astrophysical Journal)
Recent works suggest that, in multiplanetary systems, a close-in exoplanet can sometimes avoid becoming tidally locked to its host star if it is captured into a secular spin–orbit resonance with a companion planet. In such a resonance, the planet remains at a subsynchronous spin rate and an appreciable obliquity (the planet’s spin–orbit misalignment angle). However, many of these works have only considered planets with fluid-like rheologies. Recent observations suggest that planets up to a few Earth masses may be rocky and thus may have an appreciable rigidity. In this work, we study the spin–orbit dynamics of such rigid planets using a linear dissipative tidal model and not enforcing principal-axis rotation about the body’s shortest principal axis. We identify a new class of spin–orbit resonances when the planet spins at twice its orbital frequency. These resonances exist at nonzero obliquity and spontaneously excite non-principal-axis rotation upon resonance capture. While these resonances eventually disappear as tidal dissipation damps the obliquity to zero (and the body returns to principal-axis rotation), they still modify the spin evolutionary history of the planet. Such resonances may enhance the prevalence of secular spin–orbit resonances in exoplanetary systems.